Determination of Total Phenolic, Total Flavonoid, and Antioxidant Activity of India Onion Extract (Indonesian Journal of Chemical Science, 2022)
Degenerative diseases can be triggered by free radicals. The disease can be inhibited by antioxidant compounds that can neutralize and destroy free radicals. The content of antioxidant compounds can be found in the genus Allium, one of which is the Indian red onion. Knowing the antioxidant activity, total phenolics, and total flavonoids of Indian shallot extract was the aim of this study. The extraction process was carried out from three solvents, namely dichloromethane, ethyl acetate, and 96% ethanol, using the multilevel maceration method with different levels of polarity. The samples tested included testing antioxidant activity using the DPPH method, total phenolics using the Folin Ciocalteu method, and total flavonoids using the aluminum chloride calorimetric method. The results showed that there were no phenolic and flavonoid compounds that had the potential as antioxidants in the dichloromethane and ethyl acetate extracts. Total phenolics, total flavonoids, and IC50 values ​​in the ethanol extract were 2,381 mg GAE/g extract, respectively; 0.330 mg QE/g extract, and 297.8689 ppm. The IC50 value obtained is classified as a weak antioxidant.